Pharmacological comparison of a nonhuman primate and a rat model of oxaliplatin‐induced neuropathic cold hypersensitivity. Issue 1 (8th February 2016) - Shidahara, Yuka; Ogawa, Shinya; Nakamura, Mari; Nemoto, Shingo; Awaga, Yuji; Takashima, Miyuki; Hama, Aldric; Matsuda, Akihisa; Takamatsu, Hiroyuki
Abstract: Oxaliplatin is a first‐line treatment for colorectal cancer. However, shortly following treatment, cold‐evoked hypersensitivity appears in the extremities and over time, the pain is such that oxaliplatin dosing may need to be markedly reduced or even terminated. There is currently a lack of efficacious treatments for oxaliplatin‐induced peripheral neuropathy, which is due in part to the difficulty in translating findings obtained from preclinical rodent models of chemotherapy‐induced peripheral neuropathy. Nonhuman primates (NHP) are phylogenetically closer to humans than rodents and may show drug responses that parallel those of humans. A significant decrease in tail withdrawal latency to 10°C water ("cold hypersensitivity") was observed beginning 3 days after intravenous infusion of oxaliplatin (5 mg/kg) in Macaca fascicularis . A single treatment of duloxetine (30 mg/kg, p.o.) ameliorated oxaliplatin‐induced cold hypersensitivity, whereas pregabalin (30 mg/kg, p.o.) and tramadol (30 mg/kg, p.o.) did not. By contrast, in rats, no significant cold hypersensitivity, or increased responsiveness to acetone applied to the hind paws, was observed 3 days after the first injection of oxaliplatin (5 mg/kg, i.p., once per day, two injections). Therefore, rats were tested after six treatments of oxaliplatin, 17 days after the first treatment. All analgesics (30 mg/kg, p.o.) significantly ameliorated cold hypersensitivity in rats. The activity of analgesics in the oxaliplatin‐treated macaques parallel clinical findings. The current results indicate that the NHP could serve as a bridge species to improve translatability of preclinical findings into clinically useful treatments for oxaliplatin‐induced peripheral neuropathy.